2022
DOI: 10.1039/d2dt02532a
|View full text |Cite
|
Sign up to set email alerts
|

CuCoNi–S anchored CoMoO4/MoO3 forming core–shell structure for high-performance asymmetric supercapacitors

Abstract: CoMoO4/MoO3@CuCoNi–S is prepared by hydrothermal and electrodeposition methods. It offers promising supercapacitor properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Obviously, the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode displays the maximum specific capacitance among its contenders. Compared with reported similar literatures, 49–56 the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode displays superior capacitive performance (Table S1†). Fig.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Obviously, the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode displays the maximum specific capacitance among its contenders. Compared with reported similar literatures, 49–56 the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode displays superior capacitive performance (Table S1†). Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Obviously, the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode displays the maximum specific capacitance among its contenders. Compared with reported similar literatures, [49][50][51][52][53][54][55][56] Generally, in the initial stage of the cyclic test, the electrode material will generate a self-activation process, the activity of the excited material increases, and the specific capacitance has an obvious enhance compared with the initial specific capacitance. To illustrate the increase in capacity, we measured the XRD of the Ni 3 S 2 /Co 9 S 8 /NiS-7 electrode after 1600 cycles (Fig.…”
Section: Dalton Transactions Papermentioning
confidence: 93%
“…10 Due to the significant increase of the Co 3+ content, the peak of Co 2p shifted to higher binding energy. 26,27 The S 2s and Mo 3d 5/2 peaks of Mo 3d still exist, indicating that the Redox reaction of Mo is reversible during charge and discharge. 10,38 The disappearance of the Mo 3d 3/2 peak may be due to the pulverization of the NiMOS 4 shell due to volume expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent achievements have demonstrated that the core-shell heterostructures are more excellent, especially taking hollow nanotubes as cores and hierarchical nanosheets as the shell, which can shorten the ion diffusion path and buffer the volume change during the chargedischarge processes, respectively. [24][25][26][27] Therefore, in order to increase the energy storage capacity, hollow structure arrays can be introduced into transition metal sulfide composites with a core-shell structure to increase the pathway for ion diffusion and improve the energy density of supercapacitor devices.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 In general, there are many ways to enhance the performance of TMO electrodes, like the addition of carbon-based material, 39 incorporation of different transition metal cations, 40 and making hybrid morphology. 41 Flower-like hybrid morphology of FeCo 2 S 4 / reduced graphene oxide demonstrated very high conductivity and delivered an energy density of 88.2 W h kg −1 . 7 100% capacitance retention was achieved for the supercapacitor by making the composite of ZnO and reduced graphene oxide.…”
Section: Introductionmentioning
confidence: 99%